Stress, illness perceptions, behaviours and healing in venous leg ulcers: findings from a prospective observational study - Walburn, Jessica; Weinman, John; Norton, Sam; Hankins, Matthew; Dawe, Karen; Banjoko, Bolatito; Vedhara, Kavita (Wolters Kluwer, 2017)
Objective: To investigate the impact of stress, illness perceptions and behaviours on healing of venous leg ulcers.